Development of a self-report measure to assess sleep satisfaction: Protocol for the Suffolk Sleep Index (SuSI) - Protogerou, Cleo; Gladwell, Valerie; Martin, Colin (Frontiers in Psychology, 2022)
Good sleep is essential for health but there is no consensus on how to define and measure people’s understanding of good sleep. To date, people’s perceptions of a good night’s sleep have been, almost exclusively, conceptualized under the lens of sleep quality, which refers to objective characteristics of good sleep, such as such as ease and time needed to fall asleep, hours of sleep, and physical symptoms during sleep and upon awakening. A related, yet different construct, sleep satisfaction, refers to perceived positive affect about one’s sleep experience and has, to date, received little attention. This research focuses on sleep satisfaction, rather than sleep quality, and aims to develop a self-report measure to assess sleep satisfaction in an English adult population. As the measure will be developed in Suffolk, England, and its primary intended users are Suffolk community members, it is labelled the Suffolk Sleep Index (SuSI). The SuSI will draw from principles of community-based participatory research, following a seven-phase developmental process comprising literature review, interviews with Suffolk community members, synthesis of literature review and interview findings, pre-testing, pilot-testing, scale evaluation, and refinement. The present research will also investigate indices related to sleep satisfaction, including the community’s general health status, lifestyle factors and socio-economic status. The research will add to the limited, yet emerging body of research on perceived sleep satisfaction and its measurement. To our knowledge a valid and reliable sleep satisfaction self-report measure has not been developed in the UK previously.